The genus Allochrusa: a comprehensive review of botany, traditional uses, phytochemistry, and biological activities - Mamadalieva, Rano; Khujaev, Vahobjon; Šoral, Michal; Mamadalieva, Nilufar Z.; Wink, Michael (Diversity, 2023)
The genus Allochrusa (Caryophyllaceae) comprises nine species, which are native to Central Asia, Turkey, Iran, Afghanistan, and the Caucasus. They have been used in folk medicine and in the preparation of various sweets and detergents, especially in Asian countries. A diversity of secondary metabolites has been reported from the genus Allochrusa, including triterpene glycosides, ecdysteroids, flavonoids, volatile compounds, fatty acids, polysaccharides, pectins, hemicelluloses, and other phytochemicals. In vitro and in vivo pharmacological studies on isolated compound fractions and extracts from Allochrusa species showed anti-inflammatory, adjuvant, hemolytic, cytotoxic, antifungal, analgesic, antioxidant, and other activities. In this review, the chemical compounds and diverse biological activities of the Allochrusa genus are summarized.
Gesehen am 01.08.2023